Utilisation of drugs for the treatment of psychiatric diseases in the pediatric population: focus on off-label use - Pesiou, Stella; Barcelo, Rafel; Fradera, Marc; Torres, Ferran; Pontes, Caridad (Frontiers in Pharmacology, 2023)
Psychotropics are increasingly used in pediatrics, often as off-label. The guarantees of safety and efficacy are not always granted in clinical practice compared to adult authorised indications. A retrospective observational study was done to estimate the prevalence of psychotropic use in pediatric subjects of Catalonia (Spain). Anonymised data on dispensation of psychotropics to pediatric patients, demography and other related data were obtained by the local healthcare management for the period 2008-2017. Estimation of off-label use was done through description of drug dispensations with no authorised use related to age range. The prevalence of psychotropics was 40.8-64.2 per 1,000 pediatric inhabitants. Hydroxyzine-only represented two thirds of dispensations, and when removed, the prevalence dropped to 26.4-32.2 per 1,000 pediatric inhabitants. Adolescents and boys were more likely to receive a psychotropic. Psychostimulants had the highest exposure rate, mainly due to methylphenidate. Off-label use was observed in 12% of subjects, corresponding to 4.6% of all dispensed psychotropics with boys being more exposed. The proportion of off-label use vs labelled use was higher in younger populations. Aripiprazole had the highest off-label frequency. Our data support the frequent reality of off-label use in pediatrics, despite the potential underestimation related to the selected off-label definition. There is an urgent need to systematically ascertain effectiveness and any potential adverse events in the off-label pediatric setting, and to generate valuable information for risk-benefit assessment in these populations where extrapolation from adults is not reliable.